The Effect Of Competency And Work Motivation On Employee Performance Of PT. XYZ - Camelia Yuliana Sitorus; Suroso; Flora Patricia Anggela; Benny Gunawan (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — The study aims to determine the influence of Competence and Work Motivation on Employee Performance, highlighting their roles in achieving the organization’s vision and mission. Research method—This research employs descriptive and verification analysis methods with a quantitative approach. A nonprobability sampling method using purposive sampling technique was applied, gathering data through questionnaires distributed via Google Forms to 78 respondents from the production division of PT XYZ. The respondent selection was based on the Slovin formula, with a population of 352 employees. Data analysis was conducted using multiple regression analysis with SPSS software version 23. Result— The analysis reveals a positive and significant effect of both Competence and Work Motivation on Employee Performance when considered individually. Additionally, a simultaneous positive and significant effect of both variables on Employee Performance was confirmed. Conclusion— Competence and Work Motivation are crucial factors that significantly enhance Employee Performance, contributing to the overall success of the organization.